ANALISIS EFEKTIVITAS GAYA KEPEMIMPINAN (Studi pada Kantor Camat Ampenan) - Nizar Hamdi; Zulkarnaen Zulkarnaen (Sekolah Tinggi Pariwisata Mataram, 2021)
This study is a descriptive study thataims to determine the leadership styleand also to examine the effectiveness of leadership styles adoptedby leaders at the Head Office Ampenan Mataram.This study used qualitative analysis to determine employee responses to the style or level of leadership styles used by leaders (sub-district) as well as adjustments to the style of leadership in order to examine the effectiveness of the leadership (Head). To help analyze the data used method Adaptibility Leader and Style Inventory (Lasi). Based onthe results of data analysis and discussion of research resultsobtained have been described as follows: 1).Leaders use leadership styles (Head) is a style of consultation and included in thestyle of the second (G2) selected by the employee by the number of 11 respondentsor by a percentage rate of 64.70%. 2). Consultation style has a positive influence onthe maturity level of an employee or employees by thenumber of employees who choose this style showed positive effectiveness of aotal of 11 or 64.70% to the level of effectiveness of thescore +1 to +11, meaning that leadership style is in accordancewithmaturity level employees or employees who are included in thelowcategory(M2) and effective. 3). Consultation style and includesthesecond force level(G2) is to provide direct behavior, because they are able to provide behavioralsupport to strengthen the capacity and astyleappropriate for individuals employed on a maturity level like thisbecause almost all directions is still low to moderate (M2) ispeople who are unable but willing to take responsibility and have confidence but lackthe skills.